2018
DOI: 10.1002/hbm.24483
|View full text |Cite
|
Sign up to set email alerts
|

The top‐down regulation from the prefrontal cortex to insula via hypnotic aversion suggestions reduces smoking craving

Abstract: Hypnosis has been shown to have treatment effects on nicotine addiction. However, the neural basis of these effects is poorly understood. This preliminary study investigated the neural mechanisms of hypnosis‐based treatment on cigarette smoking, specifically, whether the hypnosis involves a top‐down or bottom‐up mechanism. Two groups of 45 smokers underwent a smoking aversion suggestion and viewed smoking‐related pictures and neutral pictures. One group underwent functional magnetic resonance imaging scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 68 publications
(86 reference statements)
1
8
0
2
Order By: Relevance
“…The results showed that the reward, executive control, and interoceptive awareness systems are highly coupled in RGUs when exposed to reward stimuli, while the association does not work in individuals with IGD, which reveals that positive correlations among the tripartite activities may be the major foundation for maintaining relative balances among the systems. This is complementary with previous research results showing that functional connectivity between the striatum and the prefrontal cortex (Becker et al, 2017;Forbes, Rodriguez, Musselman, & Narendran, 2014), as well as between the insula and prefrontal cortex (Dong, Liu, et al, 2019a;Li et al, 2019), are reduced in addicted individuals, reflecting enhanced internal craving and reward sensitivity as well as weak executive control. In addition, given that these couplings among systems are only observed in healthy groups, we infer that it may be an important marker for predicting the risk of addiction and even play a causal role in the transition to IGD.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results showed that the reward, executive control, and interoceptive awareness systems are highly coupled in RGUs when exposed to reward stimuli, while the association does not work in individuals with IGD, which reveals that positive correlations among the tripartite activities may be the major foundation for maintaining relative balances among the systems. This is complementary with previous research results showing that functional connectivity between the striatum and the prefrontal cortex (Becker et al, 2017;Forbes, Rodriguez, Musselman, & Narendran, 2014), as well as between the insula and prefrontal cortex (Dong, Liu, et al, 2019a;Li et al, 2019), are reduced in addicted individuals, reflecting enhanced internal craving and reward sensitivity as well as weak executive control. In addition, given that these couplings among systems are only observed in healthy groups, we infer that it may be an important marker for predicting the risk of addiction and even play a causal role in the transition to IGD.…”
Section: Discussionsupporting
confidence: 81%
“…Another study on IGD demonstrated that the coupling between decreased DLPFC activity and increased insula activity might underlie continuous addictive behaviors (Dong, Liu, Zheng, Du, & Potenza, 2019a). Additionally, increased connectivity between the insula and the DLPFC was observed in individuals addicted to nicotine after treatment (Li et al, 2019). These findings suggests that dysregulation of the neural response in addicted individuals might be related to this relative imbalance among the tripartite systems.…”
Section: Introductionmentioning
confidence: 96%
“…Functional imaging studies have shown that high ratings of craving positively correlate with insular activity, suggesting that craving is reflected by neural activity of the endogenous reward system [66,67]. As an indirect effect of DLPFC stimulation, modulation of insular activity could be one explanation for the observed reduction in craving, which could be accomplished by prefrontal-directed top-down modulation and cognitive down-regulation of craving [66,68,69]. Previous studies in drug addiction show that indeed cognitive inhibition and suppression of drug-related cues are associated with reduced metabolism in the insula [70] and subcortical structures, such as the ventral striatum [68].…”
Section: Taskmentioning
confidence: 99%
“…Previous research has reported that individuals with Internet gaming disorder (IGD) showed lower RSFC between medial orbitofrontal cortex and VTA compared with healthy controls 15 . Li's study suggested that decreased smoking craving via hypnotic treatment may arise from the top‐down regulation of the prefrontal to insula 16 . Combined, tobacco addiction is thought to be linked to the reward system and the top‐down circuit plays a vital role in the reward system including PFC, ventral striatum, insula, and midbrain 17 .…”
Section: Introductionmentioning
confidence: 99%